Post-COVID-19 and other changes in the health status of children and adolescents associated with the transmission of COVID-19 - Dmytryshyn , Olha; Marushko , Yurii (The Ukrainian Scientific Medical Youth Journal, 2023)
determining the state of physical and psycho-emotional health of children and adolescents who have suffered from COVID-19 is an urgent diagnostic problem, the solution of which will provide an opportunity for early detection of long-term and distant consequences of the coronavirus disease. The aim is to analyze the frequency, duration, and clinical manifestations of post-COVID-19 in children and adolescents, as well as other changes in health status associated with having experienced COVID-19. Materials and methods: 155 children aged 6 to 18 took part in the study. Among them, 120 children with a confirmed diagnosis of COVID-19 in the anamnesis and a period after COVID-19 of more than 12 weeks (the main group) and 35 somatically healthy children of the same age who did not suffer from COVID-19 and formed the control group. The distribution of children in the main group took place taking into account the severity of COVID-19. Children who contracted mild COVID-19 formed the first group (n=49). Group II included children who suffered from COVID-19 of moderate severity (n=40). Group III included children who contracted COVID-19 with a severe course (n=31). General clinical (analysis of anamnesis data, objective examination, assessment of complaints and identification of post-covid symptoms), survey (assessment of the general state of health of children before and after COVID-19, assessment of the level of fatigue), statistical research methods (MedStat statistical packages, EZR). Results: post-COVID-19 was detected in 46 children (38.3%) of the main group. Among the children of the I group, the post-COVID-19 condition was determined in 10 children (20.4%), in the II group - in 14 (35.0%) children, and the III group - in 22 (71.0%) children. The median duration of the post-COVID-19 in the children of the I group was 3.5 months [3; 4], in the II group - 5 months, in the III group - 7 months (p<0.05 between groups when performing multiple comparisons according to Dunn's test). The median duration of post-COVID-19 symptoms in children of the main group was 5 months. The average value (X) and standard deviation (±SD) of the number of symptoms of post-COVID-19 in children of the main group were 5.17±2.7 symptoms: in children of the I group - 1.70±0.82 symptoms, in the II group - 4,29±1.38 symptoms, in the III group - 7.32±1.76 symptoms. The most frequently recorded post-COVID-19 symptoms were anxiety (15; 95% CI 9.1-22.0), increased fatigue (13.3; 95% CI 7.8-20.0), sleep disturbances (12 .5; 95% CI 7.2-19.1), depressive disorders (11.7; 95% CI 6.5-18.1), impaired concentration of attention (10.8; 95% CI 5.9-17,1). Analysis of survey data on changes in physical and psychological/emotional health status revealed a worsening of outcomes after COVID-19 compared to the period before coronavirus disease. The median score on the Chalder fatigue scale in the children of the main group was 12, in the control group – 7 (p<0.001 by the Wilcoxon W-test for two independent samples). Conclusions: Acute COVID-19 harms the health of children and adolescents, which can be manifested by the development of a post-COVID-19. The risk of developing post-COVID-19 depends on the degree of severity of the transferred coronavirus disease. The post-COVID-19 condition was detected in 71% of children who suffered from severe COVID-19, which is significantly higher compared to children who suffered from COVID-19 of mild and moderate severity. Children with COVID-19 scored worse on the Chalder Fatigue Scale than healthy children. There was also a tendency to worsen the assessment of the health status of children in a comparative analysis of the physical and psychological/emotional components before and after COVID-19.